C9orf72-ALS mutation drives basal mitophagy impairments in iNeurons - Lee, James A. K.; Moutin, Chloe; Granger, Sarah; Roome, Katie; Shaw, Allan; Allen, Scott P.; Ferraiuolo, Laura; Shaw, Pamela J.; Mortiboys, Heather (Frontiers in Cellular Neuroscience, 2026)
IntroductionALS is a neurodegenerative disorder characterized by progressive upper and lower motor neuron loss. A GGGGCC hexanucleotide repeat expansion (HRE) in the C9orf72 gene is the most common mutation found in populations of European descent. Mitochondrial dysfunction has been observed in C9orf72-ALS patients and models of the disease, however, reports on mitochondrial clearance via mitophagy in C9orf72-ALS are limited.ResultsiNeurons from C9orf72-ALS patients displayed reduced mitochondrial membrane potential and reduced basal mitophagy, due to reductions in autophagosome production and reduced ULK1 recruitment to mitochondria. No consistent changes to PINK1/Parkin or BNIP3 mitophagy pathways were observed.ConclusionOur data show that certain aspects of mitochondrial function is impaired in C9orf72-ALS patient iNeurons. An in-depth characterization of mitophagy suggests that a deficit in autophagosome production is responsible and provides further evidence that toxic gain-of-function mechanisms in C9orf72-ALS are responsible for autophagy deficits.